(untitled) (The Journal of Psychology and Sociology, 2016)
The paper discusses the development of small and medium-sized businesses the formation of the personnel management system. With regard to the management characteristics of small and medium-sized businesses, we presented the results of a psychological experiment. We, as a pilot area took an external advertising agency SP “Zhanbolat”, LLP “World Fast Food.” First of all, we have described in the article the results of a study on the heads of institutions of small and medium businesses in the market. Then personnel analysis were conducted. Comparing the results, published in the end, it was held, and the identification and analysis of labor relations. The article also provides a solution of the work tasks carried out to determine the management processes and methods. In general, the staff and managers were investigated by the following methods: “The head of the eyes of employees”, the “Company value-oriented community diagnosis”, “adaptation of workers”, “Head of business and personal qualities. Psychological management and staff and management, it is treated as a special mechanism for a long time. The concept of management and employees, a well-known consumer psychological approaches to the new system, it became possible to conclude a number of important all-purpose (branding) is the distribution of goods in the case of imaging, human resources and management and psychological proved to be closely associated with the brand in the same kind of relationship.